2019
DOI: 10.1111/cns.13146
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of leonurine against ischemic stroke in mice by activating nuclear factor erythroid 2‐related factor 2 pathway

Abstract: Aims Leonurine has been shown to trigger antioxidant responses during ischemic stroke, and nuclear factor erythroid 2‐related factor 2 (Nrf‐2) imparts protective effects against oxidative injury. The present study has determined that leonurine prevents ischemic injury of brain tissues via Nrf‐2 pathway activation. Methods Male ICR mice and Nrf‐2−/− mice were subjected to permanent middle cerebral artery occlusion (pMCAO) and received leonurine treatment at 2 hours after pMCAO by intraperitoneal injection. Neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 49 publications
0
29
0
Order By: Relevance
“…Reduced glutathione and total glutathione/oxidized glutathione are the main dynamic indicators of cellular redox status ( Aquilano et al, 2014 ). Furthermore, GPx is a specific catalase for the hydrogen peroxide reduction of reduced glutathione and its activity represents the rate at which GSH is catalyzed ( Xie et al, 2019 ). In this study, GPx activity, GSH levels, GSH/GSSG ratio, and SOD levels were decreased in stroke patients, but MDA levels and LPO levels were increased.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced glutathione and total glutathione/oxidized glutathione are the main dynamic indicators of cellular redox status ( Aquilano et al, 2014 ). Furthermore, GPx is a specific catalase for the hydrogen peroxide reduction of reduced glutathione and its activity represents the rate at which GSH is catalyzed ( Xie et al, 2019 ). In this study, GPx activity, GSH levels, GSH/GSSG ratio, and SOD levels were decreased in stroke patients, but MDA levels and LPO levels were increased.…”
Section: Discussionmentioning
confidence: 99%
“…It also binds to specific deoxyribonucleic acid antioxidant response elements (AREs) to initiate the transcription of cytoprotective genes such as heme oxygenase-1 ( HO-1 ; also known as Hmox1 ), superoxide dismutase family members (SODs) and glutathione reductase ( Gsr ) in the nucleus ( Chen et al, 2018 ). It has been reported that an increased level of Nrf2 exerts neuroprotective effects in TBI ( Caglayan et al, 2019 ) and neurodegenerative diseases due to amelioration of oxidative damage ( Xie et al, 2019 ). Thus, modulation of Nrf2 is a potential strategy to attenuate TBI-induced oxidative damage and mitochondrial dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, antioxidant systems also exert protective effects on blood vessels. For instance, ginkgolide [ 166 ] and leonurine [ 167 ] promote angiogenesis via upregulated VEGF expression. Fourthly, BBB integrity can be protected by several antioxidants, including astragaloside IV [ 168 ], Osthole [ 169 ] and the Chinese herbal medicine formula, Tao Hong Si Wu Decoction[ 170 , 171 ].…”
Section: Antioxidants and Antidepressants In Stroke/depressionmentioning
confidence: 99%